A new species of Efibula (Polyporales, Basidiomycota) from China - Ma, Rui-Xin; Shi, Zheng-Jun; Zhao, Chang-Lin (Phytotaxa, 2020)
Efibula yunnanensis is proposed as a distinct new species based on morphological and molecular phylogenetic data. The species is characterized by an annual growth habit, resupinate basidiomata with smooth, cream to pale brown hymenial surface, a monomitic hyphal system with thin-walled, simple septate generative hyphae and ellipsoid, hyaline, thin-walled, smooth, IKI-, CB-basidiospores. The phylogenetic analyses based on ITS sequence data analyses revealed that E. yunnanensis was sister to a clade comprised E. clarkii and E. gracilis, and then grouped with E. americana and E. tuberculata.